2018
DOI: 10.32693/jgk.15.2.2017.402
|View full text |Cite
|
Sign up to set email alerts
|

Morfodinamika Jangka Pendek Pendangkalan Di Alur Pelayaran Barito, Kalimantan Selatan

Abstract: Potensi sumber daya mineral di pulau Kalimantan pada umumnya berada di hulu-hulu sungai yang relatif jauh dari pantai. Potensi ini pada umumnya telah dieksplorasi bahkan dieksploitasi, namun kendala yang umum dihadapi adalah pengangkutan hasil tambang tersebut. Keterbatasan sarana dan prasaran transportasi darat akibat kondisi alam yang berawa sehingga menyebabkan pilihan jatuh kepada transportasi sungai yang lebih murah efektif dan efisien. Kendala yang umum terjadi pada system transportasi melalui sungai ada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…On the other hand this study also found several factor that need to be improved such as settlements on the water have not been organized, leaving a slum and dirty impression (Pradana: 2020); An alarming rate of river silting due to upstream deforestation and waste from settlements on water (Novico: 2017); the condition of the river is also dirty due to the absence of a good waste disposal system from settlements over water (Widiastiti: 2008); lack of supporting infrastructure such as docks, lodging, proper culinary centers in most floating markets; difficult access problems to most floating markets on the Barito River (Pradana: 2020); actions of thuggery and illegal levies that disturb the comfort of tourists (Pradana: 2020); the lack of human resources quality (Normaleni: 2016); limited offered products, and services (Pradana: 2020); most of the boats offered have not prioritized tourist comfort and seem unkempt (Pradana: 2020); and last lack of cultural tourism governance (Pradana: 2020).…”
Section: Swot Analysis and Strategy For Floating Market Development O...mentioning
confidence: 78%
“…On the other hand this study also found several factor that need to be improved such as settlements on the water have not been organized, leaving a slum and dirty impression (Pradana: 2020); An alarming rate of river silting due to upstream deforestation and waste from settlements on water (Novico: 2017); the condition of the river is also dirty due to the absence of a good waste disposal system from settlements over water (Widiastiti: 2008); lack of supporting infrastructure such as docks, lodging, proper culinary centers in most floating markets; difficult access problems to most floating markets on the Barito River (Pradana: 2020); actions of thuggery and illegal levies that disturb the comfort of tourists (Pradana: 2020); the lack of human resources quality (Normaleni: 2016); limited offered products, and services (Pradana: 2020); most of the boats offered have not prioritized tourist comfort and seem unkempt (Pradana: 2020); and last lack of cultural tourism governance (Pradana: 2020).…”
Section: Swot Analysis and Strategy For Floating Market Development O...mentioning
confidence: 78%
“…The impact of domestic waste that is directly discharged into rivers can cause silting of river channels in Indonesia (Indrawati, 2011;Marliani, 2015;Zulfahmi et al, 2016). The Barito River is one of the largest and longest rivers in Indonesia undergoing a process of silting due to domestic waste, so it is necessary to periodically dredge because it is a transportation route for passenger ships, cargo, and coal which is very important to support the economy of South Kalimantan Province (Novico et al, 2018). The impact of domestic waste that is directly discharged into the river causes the large cost of clean water treatment that occurs in the Banjarmasin City area, due to factors of physical, chemical, and biological pollution (Auliani, 2011;Budi and Tantyonimpuno, 2006)…”
Section: Amount Of Domestic Waste Pollution In Banjarmasin City River...mentioning
confidence: 99%
“…The rapid erosion process that occurs is increasing the sedimentation process in river basins, resulting in shallowing river flow. This shallowing causes a decrease in the capacity of river basins, so that excess volume of water during the rainy season will overflow out of the river channel and flood the areas around the river channel, while in the dry season the dust is very concentrated floating around the mine road [12].…”
Section: Introductionmentioning
confidence: 99%